Problem Based Learning Implementation to Increase The Students’ Conceptual Understanding of Elasticity - Muhammad Reyza Arief Taqwa; Lugy Rivaldo; Revnika Faizah (Formatif: Jurnal Ilmiah Pendidikan MIPA, 2019)
This study aims to determine the effectiveness of the implementation of problem based learning in elasticity and Hooke's law. The design of this study is the Embedded Experimental Model with a mixed method approach. Implementation was carried out at SMAN 5 Jambi in 34 students of Class XI IPA in the 2018/2019 school year. From the results of the analysis obtained there was an increase in conceptual understanding scores from 42.31 at pretest became 57.01 at posttest. The results of different tests using paired sample t-test were obtained t = - 4,901 (sig. 0,000) so it can be concluded that the pretest and posttest scores is differ significantly. Obtained the value of N-gain = 0.255 and effect size (d) = 0.930 shows an increase in the medium category and there is the influence of the implementation of the problem based learning model that is strong enough to increase understanding of students' concepts. Although students and teachers experience obstacles in implementing problem based learning learning models, this learning must continue to be carried out with improvement so students are accustomed to construct their own knowledge.